2013
DOI: 10.1021/jp403998u
|View full text |Cite
|
Sign up to set email alerts
|

Binding of O2 and NO to Heme in Heme-Nitric Oxide/Oxygen-Binding (H-NOX) Proteins. A Theoretical Study

Abstract: The binding of O2 and NO to heme in Heme-Nitric Oxide/OXygen-binding (H-NOX) proteins has been investigated with DFT as well as dispersion-corrected DFT methods. The local protein environment was accounted for by including the six nearest surrounding residues in the studied systems. Attention was also paid to the effects of the protein environment, particularly the distal Tyr140, on the proximal iron–histidine (Fe–His) binding. The Heme–AB (AB = O2, NO) and Fe–His binding energies in iron porphyrin FeP(His)(AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 75 publications
2
16
0
Order By: Relevance
“…Different functionals (BLYP, revPBE, PW91) were tested for the calculations, but we faced several convergence or accuracy issues. The combination of the PBE Density Functional 80 , 81 in a plane-wave pseudopotential norm-conserving (NCPP) framework available in the MT (Troullier-Martins) scheme 82 and the Kleinman-Bylander approximation for the effect of core electrons 83 , proved ideal, as it is also employed elsewhere and has shown remarkable accuracy for porphyrins and chlorophylls alike 32 , 84 , 85 .…”
Section: Methodsmentioning
confidence: 99%
“…Different functionals (BLYP, revPBE, PW91) were tested for the calculations, but we faced several convergence or accuracy issues. The combination of the PBE Density Functional 80 , 81 in a plane-wave pseudopotential norm-conserving (NCPP) framework available in the MT (Troullier-Martins) scheme 82 and the Kleinman-Bylander approximation for the effect of core electrons 83 , proved ideal, as it is also employed elsewhere and has shown remarkable accuracy for porphyrins and chlorophylls alike 32 , 84 , 85 .…”
Section: Methodsmentioning
confidence: 99%
“…A survey of the experimental techniques for determining the spin states of inorganic compounds is detailed in reference [40] Given the difficulty in characterizing the spin in ground state ferrous or ferric porphyrin complexes by experimental methods, quantum chemical calculations are very useful to provide reliable spin state predictions. In the last two decades, numerous theoretical reports have been devoted to this topic [10,30,[41][42][43][44]. It turns out that in the case of DFT-type calculations, the lowest spin state and the splitting between different spin components are dependent on the exchange-correlation functional and the size of the basis sets chosen [30].…”
Section: Spin Structure Of Fe Porphyrinsmentioning
confidence: 99%
“…9 The effect of native distal group (HIS64) and other residues as a distal group into NO, has been studied experimentally and computationally by different groups. [10][11][12][13][14][15] It has been shown that the Fe II -N-O angle is bent ($140 ), while Fe III -N-O is linear ($180 ). 16 Olson et al 10 reported that ligation of NO to heme is stabilized several times using hydrogen bonding to HIS64.…”
Section: Introductionmentioning
confidence: 99%
“…As stated in previous reports on the interaction of NO to Fe-porphyrin and Mb (in absence and presence of distal His), the protein environment in Mb has slight effect on the heme-NO binding strength. 15,20,21 In this study, we have considered a simplied porphyrin-iron model to decrease the computation costs. This model has been examined in our previous work (comparing to experiment) and it has been established the model is capable enough to describe the binding of small ligands to heme.…”
Section: Introductionmentioning
confidence: 99%